Development of minimum competency assessment (AKM) instruments to measure the numeration ability of seventh grade of junior high school students - Noviantini, Ni Made Hendriana; Sariyasa, Sariyasa; Ardana, I Made (International Journal of Trends in Mathematics Education Research, 2023)
Numeration is one of the competencies measured in AKM. Numerical ability in AKM is the ability to solve mathematical problems using various numbers and symbols in the context of numbers, measurements and geometry, data and uncertainty, and algebra that uses cognitive processes of knowing, applying, and reasoning in personal, socio-cultural, and scientific contexts. This research is a type of development research that aims to produce a product in the form of an expanded multiple-choice test instrument to measure the numeracy skills of seventh-grade junior high school students. The development model used is the four-D Model by Thiagarajan which is modified into three stages (define, design, and develop). The scoring technique uses polytomies and involves 70 students as test subjects for the instrument. The results showed that (1) the characteristics of the AKM instrument developed in terms of context and cognitive level were close to the estimated percentage and covered four domains with their respective minimum competencies, (2) item validity values ranged from 0.274 to 0.743, (3) the instrument reliability coefficient is 0.88, (4) the level of difficulty is 8% easy, 80% is moderate and 12% is difficult, (5) the discrepancy index is between 0.43 to 0.78, (6) 92% questions have good distractor effectiveness.